Body Dysmorphic Symptoms and its Clinical Correlates in Young Adults at a Medical College of Western India: A Cross-sectional Study - Lakhan R. Kataria; Nisheet Maheshkumar Patel; Grishma V. Savaliya; Apoorva M. Bang; Dharti D. Shah (Journal of Integrated Health Sciences)
Introduction: An obsession with perceived physical appearance defects is the hallmark of body dysmorphic symptoms (BDSs), a complicated and multidimensional psychological condition that frequently results in severe discomfort and functional impairment. Previous research indicates that these symptoms are correlated with symptoms of depression, anxiety, and stress. Aim: The aim of this study was to determine how common BDSs are among young people and investigate how they relate to demographics, social media use, social interaction, peer and celebrity comparison, and obsessive behaviours. Material and Methods: It was a cross-sectional study among 80 youth of 18–25-year age group of a tertiary care centre university of Gujarat in June and July 2023. The study was conducted after taking their prior informed consent through an online form, and they were given to fill online questionnaire to collect sociodemographic factors in English. It also contains the Body Dysmorphic Disorder Questionnaire and the Depression Anxiety Stress Scale-21. Statistical analysis was done using Epi Info software, and statistical tests applied were mean and standard deviation, Chi-square test, and t-test. Results: Eighty youth were enrolled; among them, 56.5% had symptoms of body dysmorphia. These are more prevalent in women as compared to men, in those who frequently compare their physical appearance with peers and celebrities, and those who feel guilty after compulsive behaviour. Symptoms of depression, anxiety, and stress are more prevalent in those with BDSs. Conclusion: The prevalence of body dysmorphic symptoms and associated depressive, anxiety, and stress symptoms among youth is high providing insight into needed early identification and timely management to improve their quality of life.